Emergency Mode of Control of Rubber Belt Conveyors via PLC System Arduino Opta - Volodya Vladimirov Dzharov (International Journal of Recent Technology and Applied Science (IJORTAS), 2025)
The purpose of this article is to investigate emergency modes in conveyor belt technology, focusing on improving protections and interlocks for greater reliability when controlled by the Arduino Opta controller. The operation of a simulation model of a rubber conveyor belt using a programmable logic controller and relay-contactor groups is presented. An experimental study of the operation of a physical model of a rubber belt conveyor was carried out using installed sensors to obtain information about the condition of the facility in real time. This was done simultaneously with the optimization of the parameters of the automation model, after which the analysis and synthesis of the Ladder program for command and control was used. The visualization, based on a programmable logic controller "Arduino Opta" and sensors for obtaining process data are of different types to cover all the key elements of the rubber belt conveyor. The article highlights the characteristics, performance, requirements and operational procedure of the belt conveyor control systems, considering emergency situations such as slippage, breakage and overload. The lab bench is built to allow for the upgrade and renewal of the control system thanks to the open structure of the controller. The practical implications of this work are that based on this template, additional implementations may present an opportunity for the development of applications such as conveyor belts in the mining industry and logistics of transporting various goods and materials.